Basin-Scale Underway Quantitative Survey of Surface Microplankton Using Affordable Collection and Imaging Tools Deployed From Tara - Mériguet, Zoé; Oddone, Anna; Le Guen, David; Pollina, Thibaut; Bazile, Romain; Moulin, Clémentine; Troublé, Romain; Prakash, Manu; de Vargas, Colomban; Lombard, Fabien (Frontiers in Marine Science, 2022)
World ocean plankton quantitative biodiversity data are still severely limited due to the high cost and logistical constraints associated to oceanographic vessels and collection/analytic devices. Here, we report the first use of an affordable and open-source plankton collection and imaging kit designed for citizen biological oceanography, composed of a high-speed surface plankton net, the Coryphaena, together with a portable in-flux automated imaging device, the PlanktoScope. We deployed this kit in December 2020 along a latitudinal transect across the Atlantic Ocean on board the schooner Tara, during the first Leg of her ‘Mission Microbiomes’. The citizen-science instruments were benchmarked and compared at sea to state-of-the-art protocols applied in previous Tara expeditions, i.e. on-board water pumping and filtration system and the FlowCam to respectively sample and image total micro-plankton. Results show that the Coryphaena can collect pristine micro-plankton at speed up to 11 knots, generating quantitative imaging data comparable to those obtained from total, on-board filtered water, and that the PlanktoScope and FlowCam provide comparable data. Overall, the new citizen tools provided a complete picture of surface micro-plankton composition, biogeography and biogeochemistry, opening the way toward a global, cooperative, and frugal plankton observatory network at planetary scale.